Pemberdayaan masyarakat dalam meningkatkan produktivitas sapi pesisir di Nagari Taratak - Sutera Kabupaten Pesisir Selatan - Montesqrit Montesqrit; Arfai Arfai; Rusdimansyah Rusdimansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Pesisir cattle are local West Sumatra cattle that have the advantage of being resistant to disease and can survive by consuming foods that are not superior. Sutera Subdistrict is one of the centres of pesisir cattle farms in Pesisir Selatan District, West Sumatra. The existence of these pesisir cows began to decline because of the large number of pregnant females being cut and the number of breeders who left this cattle breeding business. One reason is that ineffective cattle maintenance with poor diet results in low performance and productivity, even if improved maintenance management such as good ration is provided, the productivity of the cow can be increased. Based on this, it is necessary to empower the community to raise livestock by providing rations that can meet the needs so that the productivity of cattle can be increased. The aim of this thematic KKN-PPM is how students are able to motivate and empower the community there. The method used in this achievement was the extension method and continued with demonstrations and going directly to the field. The activity carried out was technology transfer in the provision of rations for pesisir cattle, making a formulation of pesisir cattle rations as needed. The results obtained open the public's insight to maintain semi-intensive livestock by means of being grounded and their rations provided in accordance with the formulation of pesisir cattle rations made. The ration provided for pesisir cattle is in the form of a complete silage ration by utilizing a source of feed raw materials that are widely available there namely field grass, rice straw, rice bran and other feed sources. With complete silage, the ration helps farmers to be more effective in providing rations and can increase the productivity of pesisir cattle.